2012
DOI: 10.1007/s00414-012-0712-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal profiles of axonal injury following impact acceleration traumatic brain injury in rats—a comparative study with diffusion tensor imaging and morphological analysis

Abstract: Traumatic axonal injury (TAI) plays a major role in the development of neurological impairments after traumatic brain injury (TBI), but it is commonly difficult to evaluate it precisely and early with conventional histological biomarkers, especially when the patients experience short-term survival after TBI. Diffusion tensor imaging (DTI) has shown some promise in detecting TAI, but longitudinal studies on the compromised white matter with DTI at early time points (≤72 h) following impact acceleration TBI are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 42 publications
3
37
0
3
Order By: Relevance
“…Li et al observed a statistically significant gradual time-dependent increase in immunoreactivity (average density) of NF-L (up to 72 hours) in certain structures of the rat brain: the corpus callosum, internal and external capsule and pyramidal tracts [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al observed a statistically significant gradual time-dependent increase in immunoreactivity (average density) of NF-L (up to 72 hours) in certain structures of the rat brain: the corpus callosum, internal and external capsule and pyramidal tracts [15].…”
Section: Discussionmentioning
confidence: 99%
“…In majority of studies, NF-H and NF-L were researched [3][4][5]7,10,12,15,16,19,20,23,28]. Neurofilaments at the site of the brain contusion disintegrate, their complete disappearance was observed 1 to 2 weeks following trauma [10,20,22,26].…”
Section: Discussionmentioning
confidence: 99%
“…Należy zauważyć, że istnieją również takie prace, w których obserwowano nie spadek, lecz wzrost immunoreaktywności neurofilamentów po urazie [25,26]. Li i wsp.…”
Section: Myszy śWinie Koty) W Większości Przypadków Badano Podjednunclassified
“…Li i wsp. stwierdzili stopniowy, statystycznie istotny wzrost immunoreaktywności (średniej gęsto-ści) neurofilamentów lekkich -NF-L -wraz z upły-wem czasu po urazie (do 72 godzin) w takich strukturach mózgu szczura, jak: ciało modzelowate, torebka wewnętrzna i zewnętrzna czy drogi piramidowe [26].…”
Section: Myszy śWinie Koty) W Większości Przypadków Badano Podjednunclassified
See 1 more Smart Citation